Pembuatan Karya Seni Paper Quilling Bermuatan Cerita Bergambar pada Kelas V SDN 092 Bengkulu Utara - Dhea Febyola Putri Hariyana; Bambang Parmadie; Hasnawati Hasnawati (JURIDIKDAS, 2022)
This study aimed to describe the process of making and the results of paper quilling artworks containing illustrated stories in learning of Cultural Arts and Crafts class V SD Negeri 092 Bengkulu Utara. This type of research is a qualitative descriptive study, with participant observation techniques. The subjects of this study were all students of class V SD Negeri 092 Bengkulu Utara, totally 14 students, 9 female and 5 male. The research instrument used was the human instrument, by using interview, observation, and documentation guidelines. Data collection techniques in the form of observation, interviews, and documentation. The data analysis techniques used are data collection, data condensation, data display, and conclusions drawing. The validity of the data used triangulation techniques. The results of the research are (1) the process of making paper quilling artwork by using tools and materials such as glue, scissors, quilling paper rolls, quilling paper, and picture paper. Followed by rolling the quilling paper, applying glue to the rolled paper, forming the roll as desired, attaching the paper quilling roll to the picture paper, making a picture story and finally delivering the story. (2) the work of paper quilling made by students contains the principles of art, namely the principles of unity, rhythm, balance, proportion, emphasis, and harmony.